2009
DOI: 10.1002/ijc.24339
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of human papillomavirus (HPV) positive tonsillar carcinoma in Stockholm, Sweden: An epidemic of viral‐induced carcinoma?

Abstract: In the county of Stockholm, between 1970 and 2002, we have previously reported a 3-fold parallel increase in the incidence of tonsillar squamous cell carcinoma (SCC) and the proportion of human papillomavirus (HPV) positive tonsillar SCC. Here, we have followed the above parameters in all patients (n 5 120) diagnosed with tonsillar SCC during [2003][2004][2005][2006][2007] in the same area, and also in correlation to our previous data. Ninety-eight pretreatment biopsies were available and presence of HPV DNA a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

27
528
7
11

Year Published

2010
2010
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 637 publications
(573 citation statements)
references
References 32 publications
27
528
7
11
Order By: Relevance
“…In this study, we found an HPV prevalence of 24.3% in our cohort, which is lower than the prevalence in OSCC and tonsillar cancer reported for the USA (45-83%) 4,5 or northern Europe (26-93%), 5,23,24 but comparable to data for central Europe (14-33%) [25][26][27] . We considered HPV-association of samples when high risk HPV-DNA was detected along with p16INK4a expression.…”
Section: Discussioncontrasting
confidence: 68%
“…In this study, we found an HPV prevalence of 24.3% in our cohort, which is lower than the prevalence in OSCC and tonsillar cancer reported for the USA (45-83%) 4,5 or northern Europe (26-93%), 5,23,24 but comparable to data for central Europe (14-33%) [25][26][27] . We considered HPV-association of samples when high risk HPV-DNA was detected along with p16INK4a expression.…”
Section: Discussioncontrasting
confidence: 68%
“…Recent surveys from the US and Western Europe indicate an increase in the incidence of oropharyngeal cancers, particularly those of the tonsil and base of tongue [28][29][30] accumulating evidence supports the role of HPV infections in driving these upward trends [31][32][33][34][35]. As reported by others [1] HPV-positive HNSCC tends to be of oropharyngeal origin, diagnosed at a later stage, and found in younger individuals.…”
Section: Discussionmentioning
confidence: 76%
“…Incidence rates for these sites were highest among blacks and higher among nonHispanics and men than among Hispanics and women. 84,85 HPV-associated SCCHN tends to have distinct characteristics. Clinically, patients diagnosed with HPV-associated SSCHN demonstrate improved disease-specific survival.…”
Section: Role Of Chemotherapy In Human Papilloma Virus-associated Heamentioning
confidence: 99%